Pelatihan Koding dan Kecerdasan Artifisial (KKA) berbasis Scaffolded Approach bagi Guru SMA/SMK di Kabupaten Labuhanbatu Utara - Muhammad Halmi Dar; Denni M. Rajagukguk; Muhammad Iqbal Panjaitan (Marsipature Hutanabe: Jurnal Pengabdian Kepada Masyarakat, 2026)
The gap in technical and pedagogical competence among Information and Communication Technology teachers in regional areas in implementing the Coding and Artificial Intelligence curriculum posed a major challenge to supporting the digital transformation of education. This community service activity aimed to enhance the competence and self-efficacy of 20 secondary school teachers in Labuhanbatu Utara Regency through training based on the Technological Pedagogical Content Knowledge framework. The training was conducted over five days using a scaffolded approach that included learning management system orientation, plugged and unplugged hands-on practice, and contextual instructional design. The evaluation results demonstrated a significant improvement in participants' understanding, marked by an increase in the average score from 45.10 to 85.10, achieving a normalized gain average of 0.73, which fell into the high-effectiveness category. All participants successfully completed their portfolios and designed ready-to-use teaching modules. This scaffolded training proved effective in addressing the digital competence limitations of regional educators and strengthening their readiness for sustainable curriculum implementation.